The quality of internet banking : evidence from the perception of the users residing at Tawau, Sabah / Rosmina Dollin Dahlin - Dahlin, Rosmina Dollin (2007)
This paper studies the quality of internet banking website. The element of reliability, functionality and usability is measure the internet banking website quality. It is speculated it has an effect to user’s loyalty. To test this notion the study are using the evidence from the perception of the user’s residing at Tawau, Sabah. Result showed that reliability, functionality and usability is an important element that user’s consider when using internet banking website and it is appear to have a positive relationship with the user’s loyalty.